IMPLEMENTATION OF STRATEGIC MANAGEMENT FOR WASTE MANAGEMENT IN KALABAHI CITY: A Case Study at the Environmental Service of Alor Regency - Obeth Bolang; Aloysius Liliweri; Ajis Salim Adang Djaha (AGUSPATI Research Institute, 2023)
This research aimed to explain and analyze (1) the formulation of waste management strategies in Kalabahi City; (2) the implementation of waste management strategies in Kalabahi City; and (3) the control of waste management strategies in Kalabahi City. This research used a qualitative approach with a case study method. Using a purposive technique, the research location was determined to be conducted at the Environmental service of Alor Regency. The focus of this research is the implementation of strategic management with sub-research focusing on: (1) Strategy formulation, (2) Strategy implementation, (3) Evaluation/control of strategy. Informants were determined using a purposive technique. Data were obtained from both primary and secondary data sources, collected using interview, documentation, and observation techniques to be further analyzed using the Miles and Huberman analysis technique. The research results were then validated using triangulation techniques.The research results indicate that the development of strategies by Alor Regency’s Environmental Service in waste management needs to consider its strengths, weaknesses, opportunities, and threats. Based on the research findings, the current strengths of Alor Regency’s Environmental Service are the quantity of employees and their high work motivation. Meanwhile, the weaknesses of Alor Regency’s Environmental Service are the limited budget and the lack of operational support facilities. The opportunities currently available to Alor Regency’s Environmental Service include the construction of a new landfill (Final Waste Disposal Site – TPA) with more advanced waste management facilities, which can provide more options for waste management innovation. Additionally, the new budgeting period can also be a good opportunity to convince stakeholders to allocate funds for the Environmental Service's programs. On the other hand, Alor Regency’s Environmental Service also faces threats, such as low public knowledge and awareness of waste disposal and management, overlapping organizational structures in waste management and transportation, and inadequate attention to worker safety.